2017
DOI: 10.1186/s12888-017-1254-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in prevalence of psychotropic drug use and alcohol consumption among the elderly in Germany: results of two National Health Interview and Examination Surveys 1997-99 and 2008-11

Abstract: BackgroundPsychotropic drug use and alcohol consumption among older adults need to be monitored over time as their use or combined use bears risks of harms. Representative data on changes in prevalence, patterns and co-relates of substance use are lacking in Germany.MethodsParticipants were older adults (60–79 years) from two German National Health Surveys: 1997–99 (GNHIES98, N = 1,606) and 2008-11 (DEGS1, N = 2,501). Included were drugs acting on the nervous system used during the last 7 days. Alcohol consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 62 publications
(94 reference statements)
3
35
1
3
Order By: Relevance
“…This permitted automated recording of unique product identifiers and drug coding according to the WHO "Anatomical Therapeutic Chemical" (ATC) classification system [28]. Definition of psychotropic drugs has been published previously [25,29]. Briefly, we included drugs belonging to the nervous system class (ATC code N00) as well as opiates used as antitussives (ATC code R05DA) and aspirincaffeine combination preparations (ATC code N02BA71) [25,29] (Appendix Table 1a).…”
Section: Data Source: German Health Interview and Examination Survey mentioning
confidence: 99%
See 1 more Smart Citation
“…This permitted automated recording of unique product identifiers and drug coding according to the WHO "Anatomical Therapeutic Chemical" (ATC) classification system [28]. Definition of psychotropic drugs has been published previously [25,29]. Briefly, we included drugs belonging to the nervous system class (ATC code N00) as well as opiates used as antitussives (ATC code R05DA) and aspirincaffeine combination preparations (ATC code N02BA71) [25,29] (Appendix Table 1a).…”
Section: Data Source: German Health Interview and Examination Survey mentioning
confidence: 99%
“…Briefly, we included drugs belonging to the nervous system class (ATC code N00) as well as opiates used as antitussives (ATC code R05DA) and aspirincaffeine combination preparations (ATC code N02BA71) [25,29] (Appendix Table 1a). We excluded other analgesics and antipyretics such as aspirin and paracetamol (ATC code N02B), local anesthetics (ATC code N01B), homeopathic drugs, and drugs with indistinct active Community size: Rural towns (<5,000 inhabitants), small cities (5,000-<20,000 inhabitants), middle-sized cities (20,000-<100,000 inhabitants) and large cities (100,000 inhabitants or more) Region of residence: Eastern Germany (Berlin, Brandenburg, Mecklenburg-Vorpommern, Sachsen, Sachsen-Anhalt and Thü ringen); Northern Germany ingredients under the ATC class N00 [25,29]. Psychotropic drugs with herbal active ingredients were considered and coded separately under specific subgroups (S1 Table).…”
Section: Data Source: German Health Interview and Examination Survey mentioning
confidence: 99%
“…Several studies have recently reported decreasing trends in benzodiazepine use in older adults in community and NH settings . It is unclear which factors are behind this pattern.…”
mentioning
confidence: 99%
“…In Deutschland gehen laut Arzneiverordnungsreport (AVR) die BZD-Verordnungen deutlich zurück, auch die der Z-Drugs sinkt mittlerweile, allerdings langsamer [12]; diese Daten aus dem Bereich der Gesetzlichen Krankenversicherung sind allerdings mit Vorsicht zu interpretieren, weil die Verordnung von BZD und Z-Drugs häufig auf Privatrezept erfolgt, hier werden Anteile von 30-50 % berichtet [28,29]. Im Gegensatz zum AVR verzeichnen repräsentative Datenerhebungen im Rahmen der DEGS1 zwischen 1997 und 2011 eine Zunahme des Gebrauchs von Z-Drugs, wenn dieser auch geringer war als die Abnahme bei den BZD [30]. In diesen Erhebungen waren Heimbewohner nicht eingeschlossen.…”
Section: Verordnung Und Gebrauchunclassified